2020
DOI: 10.1161/circ.142.suppl_3.15651
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 15651: The Burden of Nontreatment or Undertreatment Among Non-valvular Atrial Fibrillation Patients With Elevated Stroke Risk: A Systematic Literature Review of Real-world Evidence

Abstract: Introduction: Global treatment guidelines (e.g., AHA/ACC/HRS, ESC, JCS) recommend treatment with oral anticoagulants (OACs) for patients with non-valvular atrial fibrillation (NVAF) and an elevated stroke risk, defined by CHA 2 DS 2 -VASc score ≥2. However, not all patients with NVAF and an elevated stroke risk receive guideline-recommended therapy. A systematic literature review of observational studies was undertaken based on PRISMA guidelines to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Our findings add to the timeline of real-world observations of OAC treatment for NVAF after the introduction of DOACs and are generally consistent in directionality [ 19 23 , 25 31 ]. In their cross-sectional registry study of > 400,000 patients with AF from 2008–2012, Hsu et al found that ~ 45% were treated with an OAC over the entire study period—among whom 90% were prescribed warfarin, 8% dabigatran (2010 FDA approval), and 2% rivaroxaban (2011 FDA approval) [ 20 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our findings add to the timeline of real-world observations of OAC treatment for NVAF after the introduction of DOACs and are generally consistent in directionality [ 19 23 , 25 31 ]. In their cross-sectional registry study of > 400,000 patients with AF from 2008–2012, Hsu et al found that ~ 45% were treated with an OAC over the entire study period—among whom 90% were prescribed warfarin, 8% dabigatran (2010 FDA approval), and 2% rivaroxaban (2011 FDA approval) [ 20 ].…”
Section: Discussionsupporting
confidence: 70%
“…Ko et al found that among Medicare beneficiaries, 67.1% of patients with incident AF in 2020 had not initiated an OAC within 12 months of diagnosis [ 44 ]. While legitimate considerations for contraindications due to comorbidity, polypharmacy, extremely high bleeding risk, or unobserved antiplatelet or aspirin prescription may play a role, there may also be some clinical inertia attributable to inappropriate concerns regarding older age, sex, frailty, or moderate bleeding risk, as well as suboptimal guideline awareness [ 23 , 24 , 45 ]. A study by Navar et al suggests differences at the provider‐ and health-system‐level are more of a driving factor in the underutilization of DOAC treatment than patient level factors among patients with NVAF [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the most recent recommended guidelines from the AHA/ACC/HRS 8 as well as a high proportion of patient eligibility for anticoagulation, 15 a systematic literature review of real-world evidence studies plus a recent Medicare claims analysis suggest that the proportion of NVAF patients treated with OACs remains low, with up to 51% of eligible patients not receiving OAC treatment. 16,17 A prior health economic modeling exercise estimated the financial A c c e p t e d M a n u s c r i p t implications for Medicare of increased thromboprophylaxis among Medicare-eligible patients with moderate-to-high risk of stroke. 18 However, this model was developed before the widespread introduction of DOACs, and therefore could not estimate their clinical and economic impact.…”
Section: Rationale and Objectivementioning
confidence: 99%
“…Literature-derived clinical estimates were obtained from a number of published sources, including a global systematic literature review presented at the American Heart Association Scientific Sessions 2020 in Dallas, Texas. 16 All calculations for this model were developed and executed in Microsoft Excel for Mac version 16.42.…”
Section: Accepted Manuscriptmentioning
confidence: 99%